The Effect of Probiotic Supplementation on Serum Interleukin -23 Levels among Ulcerative Colitis Patients: a Pilot Study and Secondary Output - Abu Sneineh, Awni; Agraib, Lana; Alkhatib, Buthaina; Yamani, Mohammed; Haj Ali, sara; Rayyan, Yaser; Khatib, Osama (Jordan Medical Journal, 2025)
Background and aims: Interleukin (IL)-23 has gained particular attention as a proinflammatory cytokine playing key roles in the pathogenesis of ulcerative colitis. Recently, probiotics have been used more frequently in treating ulcerative colitis for induction and maintenance of remission. This study aimed to evaluate the effect of probiotic supplementation on IL-23 levels after remission induction in mild-to-moderately active ulcerative colitis patients in Jordan. Methods: This is a pilot, multicenter, randomized, placebo-controlled, double-blind parallel-arms study. Twenty-four ulcerative colitis patients (11 men, 13 women) were randomly assigned to receive 3×1010 probiotic 10 billion active cells or three capsules of placebo daily for six weeks. Partial mayo score and serum level of IL-23 were measured at baseline and after six weeks. Results: There was a significant difference in the mean Partial Mayo score between the probiotic group and the placebo group at the end of the study (1.33 ± 0.49 vs 3.42 ± 1.78) (p<0.001). The probiotics' IL-23 level was insignificantly reduced compared to the placebo group (p>0.05). Similarly, there were no significant differences in the mean or percentage change in the IL-23 level between the two groups (p>0.05). Conclusions: Probiotic supplementation had an insignificant suppressive effect on IL-23 levels. However, it still offered a beneficial therapeutic effect for patients with ulcerative colitis, as evidenced by an improvement in the Partial Mayo score.